Development and validation of a photographic food atlas of Middle Eastern Mediterranean diet: Toward improved understanding of traditional healthy and sustainable diets - Badrasawi, Manal; Altamimi, Mohammad; Zidan, Souzan; Illner, Anne-Kathrin; Aleksandrova, Krasimira (Frontiers in Nutrition, 2023)
Background Middle Eastern Mediterranean diet (MEMD) is a traditional plant-based diet that is commonly consumed and increasingly popular, but not well studied in nutrition research. To facilitate the dietary assessment of MEMD, we developed and validated a photographic food atlas depicting a variety of foods and dishes consumed in the Middle Eastern Mediterranean region. Methods The photographic food atlas included 1002 photos of 400 types of foods and traditional dishes photographed characterizing MEMD. Foods and dishes were prepared by a professional cook and were subsequently photographed as a series of photos depicting portion size options. In a validation study, 45 individuals aged 20 to 50 years were recruited to assess portion size estimation of 25 representative food-photo series for each item. The validity of portion size estimation was assessed by comparing actual and reported estimates using Pearson or Spearman correlation tests. Sizes of the differences between estimated portions and the actual served portion sizes were calculate as mean differences and standard deviations. Results In the validation study, there was a strong correlation (r > 0.7) between estimated portion size of actual foods for 7 food items, such as pita bread, milk, labneh, and tomatoes, a moderate correlation (< 0.5 | r | < 0.7) for 12 items, such as meat, chicken, and grapes, and weak correlation (r < 0.3) for 6 items, such as seeds. Underestimation of portion sizes was more commonly observed for food items quantified when using ‘grams’ or ‘milliliters’ as a unit of measurement. In contrast, when household measurements were used, the participants tended to overestimate the portion sizes of respective foods and dishes. Conclusion We developed and validated a photographic food atlas depicting a wide variety of foods and dishes typical for the MEMD. The application of the photographic food atlas may facilitate the accurate assessment of adherence to MEMD and support the understanding of its health and sustainability aspects. Further methodological work is warranted to extend the list of food items and to evaluate the validity of the food atlas among larger and more heterogeneous groups of participants.